Dose-dependent effects of gamma radiation on the early zebrafish development and gene expression. - Selma Hurem; Leonardo Martín Martín; Dag Anders Brede; Eystein Skjerve; Rasoul Nourizadeh-Lillabadi; Ole Christian Lind; Terje Christensen; Vidar Berg; Hans-Christian Teien; Brit Salbu; Deborah Helen Oughton; Peter Aleström; et al. (PLoS ONE)
Ionizing radiation from natural sources or anthropogenic activity has the potential to cause oxidative stress or genetic damage in living organisms, through the ionization and excitation of molecules and the subsequent production of free radicals and reactive oxygen species (ROS). The present work focuses on radiation-induced biological effects using the zebrafish (Danio rerio) vertebrate model. Changes in developmental traits and gene expression in zebrafish were assessed after continuous external gamma irradiation (0.4, 3.9, 15 and 38 mGy/h) with corresponding controls, starting at 2.5 hours post fertilization (hpf) and lasting through embryogenesis and the early larval stage. The lowest dose rate corresponded to recommended benchmarks at which adverse effects are not expected to occur in aquatic ecosystems (2-10 mGy/day). The survival observed at 96 hours post fertilization (hpf) in the 38 mGy/h group was significantly lower, while other groups showed no significant difference compared to controls. The total hatching was significantly lower from controls in the 15 mGy/h group and a delay in hatching onset in the 0.4 mGy/h group was observed. The deformity frequency was significantly increased by prolonged exposure duration at dose rates ≥ 0.4 mGy/h. Molecular responses analyzed by RNA-seq at gastrulation (5.5 hpf transcriptome) indicate that the radiation induced adverse effects occurred during the earliest stages of development. A dose-response relationship was found in the numbers of differentially regulated genes in exposure groups compared to controls at a total dose as low as 1.62 mGy. Ingenuity Pathway Analysis identified retinoic acid receptor activation, apoptosis, and glutathione mediated detoxification signaling as the most affected pathways in the lower dose rate (0.54 mGy/h), while eif2 and mTOR, i.e., involved in the modulation of angiogenesis, were most affected in higher dose rates (5.4 and 10.9 mGy/h). By comparing gene expression data, myc was found to be the most significant upstream regulator, followed by tp53, TNF, hnf4a, TGFb1 and cebpa, while crabp2b and vegfab were identified as most frequent downstream target genes. These genes are associated with various developmental processes. The present findings show that continuous gamma irradiation (≥ 0.54 mGy/h) during early gastrula causes gene expression changes that are linked to developmental defects in zebrafish embryos.